COVID-19 post-vaccination in healthcare workers and vaccine effectiveness, Brazil, 2021 (Clinics, 2022)
Objects: This study aimed to describe COVID-19 cases in healthcare workers at a large tertiary hospital, after a vaccination campaign, to understand the individual characteristics, timeliness, symptomatology, and severity of the conditions.Methods: The COVID-19 reporting files from the hospital's healthcare workers and their records in the vaccine registry were analyzed, regarding vaccination status, symptoms, sociodemographic characteristics, comorbidities, and outcomes. Vaccination descriptive analysis was carried out and the impact and effectiveness of vaccination in relation to symptomatic infection and hospitalization were estimated.Results: In a total of 696 PCR-confirmed COVID-19 patients, vaccination coverage for the 1st and 2nd dose was 92.8% and 85.5%. Patients with complete doses had a mean interval of 96.8 days between vaccination and the onset of symptoms. Of the 664 participants with available clinical data, 165 had at least 1 comorbidity. During the study, 12 patients were hospitalized, 58.3% with a complete vaccination schedule. Three of this group died. The effectiveness of vaccination for symptomatic cases and hospitalization was 22.1% and 69.0%, respectively. The impact of vaccination on symptomatic cases and hospitalization was 81.4% and 89.7%, respectively.Discussion: The majority of COVID-19 cases in the study were classified as mild. The impact of vaccination for confirmed cases was significant, both in reducing the incidence of symptomatic cases and hospitalizations. The presence of comorbidities in approximately ¼ of the patients increased the risk of these individuals. The mean time interval between diagnosis and the 2nd dose of vaccine was longer in the hospitalized group, reinforcing the protective decline over longer periods.